Dynamics of players` relative positioning during baseline rallies in tennis - Carvalho, J.; Araujo, D.; Travassos, B.; Esteves, P.; Pessanha, L.; Pereira, F.; Davids, K. (Journal of Sports Sciences, 2013)
This study analysed how the relative positioning of players on court influenced patterns of interpersonal coordination in baseline rallies in tennis. We developed a model (PA index) that assigns a weight to the position of each player on court and determines a positional advantage, based on the relative proportionality between the lateral and longitudinal displacement values during rallies. To test the model, data from 27 randomly-selected baseline rallies from three ATP World Tour matches (professional tennis players' tournaments organized by Association of Tennis Professionals) on clay were analysed. Results revealed that the PA index of players on court described their interpersonal coordination dynamics during baseline rallies. It also identified the emergence of rally breaks in the interpersonal coordination patterns of competing dyads that led to a point being scored. Data suggest that positional advantage data may assist coaches in the design of training tasks to enhance players' court coverage and performance during competitive interactions, acting as a valuable tool for performance analysis in tennis.